Anthracene coupled adenine for the selective sensing of copper ions - Ghosh, Kumaresh; Sen, Tanushree (Beilstein Journal of Organic Chemistry, 2010)
Anthracene-based adenines 1 and 2 have been designed and synthesized, and their metal ion recognition properties have been established fluorometrically. Both molecules exhibit Cu2+ induced ON-OFF type signaling patterns over the other representative metal ions studied. Compound 1 exhibits 97% quenching of emission in the presence of Cu2+ whilst derivative 2 shows 81% quenching under similar experimental conditions.
Keywords: adenine-based anthracene; copper ion selective; fluorescence; metal ion recognition; PET sensory systems